2015
DOI: 10.1016/j.semcancer.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Broad targeting of angiogenesis for cancer prevention and therapy

Abstract: Deregulation of angiogenesis – the growth of new blood vessels from an existing vasculature – is a main driving force in many severe human diseases including cancer. As such, tumor angiogenesis is important for delivering oxygen and nutrients to growing tumors, and therefore considered an essential pathologic feature of cancer, while also playing a key role in enabling other aspects of tumor pathology such as metabolic deregulation and tumor dissemination/metastasis. Recently, inhibition of tumor angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
332
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(356 citation statements)
references
References 448 publications
(251 reference statements)
3
332
1
11
Order By: Relevance
“…43,44 Hypoxiainducible factor 1 (HIF-1) controls oxygen delivery (via angiogenesis) to cancer tissues. 45,46 Our previous data using hif-1adPA mice showed that hif-1a over-expression in hepatocytes led to increased steatosis, while hif-1a deletion in hepatocytes protected mice from alcohol-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Hypoxiainducible factor 1 (HIF-1) controls oxygen delivery (via angiogenesis) to cancer tissues. 45,46 Our previous data using hif-1adPA mice showed that hif-1a over-expression in hepatocytes led to increased steatosis, while hif-1a deletion in hepatocytes protected mice from alcohol-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are antioxidants, anti-angiogenic, anti-proliferative, active oxygen species scavengers, electrophiles, metal chelators, hydrogen peroxide producers, nitrosation inhibitors, and phase I detoxification enzyme modulators [25,26,43]. Flavones, flavanones, flavonols, flavanonols, isoflavones, flavanols, anthocyanidins and anthocyanins comprise the flavonoid category.…”
Section: Phenolsmentioning
confidence: 99%
“…Anthocyanidins and anthocyanins: This group includes cyanidin, delphinidin, malvidin, peonidin, and petunidin, which are found in blueberries [43,46]. Carob fruit contains delphinidin, pelargonidin and cyanidin [47].…”
Section: Phenolsmentioning
confidence: 99%
See 2 more Smart Citations